Possible Role of Platelet-Rich Plasma in the Treatment of Patients with Postherpetic Neuralgia: A Prospective, Single-Arm, Open-Label Clinical Study - Mohammed Abu El-Hamd; Shereen G. Abd Elaa; Ashraf Abdelwahab (Indian Dermatology Online Journal)
Background: Currently, no treatment can fully and finally treat postherpetic neuralgia (PHN). Aim and Objectives: This study aimed to evaluate the possible efficacy of autologous intralesional platelet-rich plasma (PRP) injection in treating patients with PHN. Materials and Methods: A prospective, single-arm, open-label clinical study was conducted on 45 patients with PHN attending the Dermatology Outpatient Clinics of Sohag University Hospital, Egypt, between November 2019 and November 2021. Patients were subjected to full clinical general and dermatologic examinations. Patient’s assessment included severity of pain through visual analogue scale (VAS), numerical rating scale (NRS), and verbal rating scale (VRS), in addition to Medical Outcomes Study 36 Item Short-Form (SF-36). Patients were treated by autologous PRP injection every 2 weeks for 2 months (4 sessions). Patients were evaluated before every session and 3- months after the last session. Results: There was a significantly decreased VAS, NRS, VRS, and SF-36 questionnaire values in the last session and three months after the last session. There was a highly significant moderate correlation between both scales (VAS and VRS) and patient’s age in years and who have aggravating factors. Likewise, there was a significant moderate positive correlation between scales (VAS and VRS) and the disease duration, medical co-morbidities, and associated myalgia. Limitations: These findings require further confirmations on more inclusive large-sized multicenter, randomized, placebo-controlled, clinical trials with longer follow-up. Conclusion: This clinical pilot study concluded that autologous intralesional PRP injection was an effective therapeutic option for patients with PHN.